Characterizing particulate matter emissions in an aviation kerosene-fueled model combustor at elevated pressures and temperatures. (1st April 2019) - Zhang, Chi; Mi, Xiaotong; Hui, Xin; Chen, Longfei; Lin, Yuzhen; Mongia, Hukam C.; Sung, Chih-Jen
Abstract: The present study investigated the characteristics of particulate matter (PM) emissions in a single-dome, Rich-Quench-Lean, model combustor under different operating conditions typical for aero-engines, with special emphasis on identifying the individual effects of pressure, temperature, and equivalence ratio on PM emissions in aero-combustors. Results showed that the number-based particle size distribution was shifted from the nucleation mode (<50 nm) to the accumulation mode (50–1000 nm) as the dome equivalence ratio increased from 0.944 to 1.267. When the dome equivalence ratio further increased from 1.342 to 1.814, the number distribution was shifted to smaller particle sizes that are dominated by the nucleation mode. With the increase of operating pressure, the PM emissions have a notably higher number concentration with smaller size particles. While increasing pressure can significantly enhance the nucleation rate yielding higher primary soot particle concentration, the hydrogen radicals that play a crucial role in the hydrogen-abstraction/carbon-addition soot surface growth mechanism are suppressed, thereby leading to the reduced surface growth rate and smaller particle size. On the other hand, the overall accumulation mode seems not being affected with increasing pressure, resulting in a similar size distribution beyond Dp > 60 nm for the different pressure cases investigated. Regarding the influence of combustion temperature, a non-monotonic response of particle geometric mean diameter with increasing primary zone average temperature was found in that particle size increased and decreased in the temperature range below and above 2270 K respectively. This non-monotonic response with temperature variation is likely caused by the competition between soot growth rate and oxidation rate. It is postulated that the increasing trend of particle size is a result of more carbonaceous particles formed under elevated temperatures providing surface areas available for the condensation of organic compounds, while the soot oxidation rate eventually overtakes at higher temperatures leading to the observed decreasing trend.